Patient Satisfaction with Physical Therapy Management: A Single City Cross-Sectional Study: Patient Satisfaction with Physical Therapy Management - Perveen, Wajida; Ali, Misbah Amanat; Javed, Asma; Kumari, Raveena; Nasir, Ayena; Sohail, Aima (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2025)
A physiotherapist deals with a variety of conditions individually and as part of Multidisciplinary rehabilitation teams. Patient satisfaction is one of the parameters used to determine the quality and efficacy of treatment given in any healthcare department. Objectives: To find out the patients' Satisfaction with Physical Therapy Management. Methods: It was an observational study conducted after ethical approval. A convenience sampling technique was used to recruit 320 participants from outpatient departments of different public and private hospitals in Sialkot, Pakistan, based on predefined eligibility criteria. Data were collected using the Med Risk patient satisfaction instrument. SPSS was used to analyze the data, with frequencies and percentages calculated for categorical responses and quantitative variables expressed as mean ± standard deviation. Results: Respondents’ characteristics showed that 202 (63.12%) were male and 118 (36.88%) female. Mean age ± SD of male was 41.82 ± 13.25 and that of female was 38.95 ± 16.55 years. Frequency (percentage) of conditions for which physiotherapy treatment was availed were: 76 (23.74%) for neurology, 107 (33.43%) for orthopedics, 79 (24.68%) for musculoskeletal and 58 (18.12%) others. Overall, 73.71% were satisfied, 10.55% were neutral, and 16.28% were not satisfied. Conclusions: A large majority of the participants were found to be satisfied with the physical therapy treatment they received.